REVOLUSI PEMBELAJARAN PARADIGMA BARU: UPAYA MENINGKATKAN KOMPETENSI GURU-GURU PAUD DALAM IMPLEMENTASI KURIKULUM MERDEKA (IKM) DI KABUPATEN BOGOR - Hasanah, Lathipah; Kusumah, Fuji Hernawati; Putri, Sepiana Permana (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
Curriculum is a key component in the development of education and the learning process in schools. The curriculum is designed to facilitate and improve the quality of learning at every level of education. However, several issues have arisen from the implementation of the Merdeka (Independent) Curriculum, including teachers not yet understanding the curriculum, which is now increasingly being implemented by early childhood education institutions (PAUD), never having received training or socialization about its implementation, and difficulties in achieving learning objectives in the classroom. The purpose of this community service activity is to enhance the competencies of PAUD teachers to enable them to develop teaching modules that align with students' needs and potential, optimize play activities as a learning method, and apply deeper assessments. The method used is action research, which consists of several steps: planning, observing, acting, and reflecting. Based on the results of the teacher satisfaction questionnaire, it can be seen that the five core materials provided (a) new learning paradigms, (b) the preparation of unit-level curricula, (c) learning outcomes, (d) assessments and learning, and (e) projects to strengthen the Pancasila student profile were well understood. Meanwhile, the results of pre-tests and post-tests also showed a significant increase in knowledge competencies, with participants scoring 25% in the pre-test and 77% in the post-test.Thus, this shows that the community service activity for implementing the Merdeka Curriculum in Bogor Regency significantly improved the competencies of PAUD teachers.